Randomised cross-over trial evaluating the short-term effects of non-invasive ventilation as an adjunct to airway clearance techniques in adults with cystic fibrosis. Issue 1 (14th April 2019) - Stanford, Gemma; Parrott, Helen; Bilton, Diana; Agent, Penny; Banya, Winston; Simmonds, Nicholas
Abstract : Introduction: Non-invasive ventilation (NIV) is used in cystic fibrosis (CF) to support airway clearance techniques (ACTs) by augmenting tidal volumes and reducing patient effort. However, the evidence base for this is limited. We hypothesised that NIV, in addition to usual ACT, would increase sputum clearance. In addition, we investigated ease of sputum clearance (EoC), work of breathing (WoB) and NIV tolerability. Methods: Adults with CF (16+ years) at the end of hospitalisation for a pulmonary exacerbation were randomised to a cross-over trial of NIV-supported ACT or ACT alone in two consecutive days. No other changes to standard care were made. The primary outcome was the total 24-hour expectorated sputum wet weight after the intervention. Spirometry was completed pre-treatment and post-treatment. Oxygen saturations were measured pre-treatment, during treatment and post-treatment. EoC and WoB were assessed using Visual Analogue Scale. Results: 14 subjects completed the study (7 male, mean age 35 [SD 17] years, mean forced expiratory volume in 1 s [FEV1 ] 49 [20] % predicted). The difference between treatment regimens was −0.98 g sputum (95% CI −11.5 to 9.6, p=0.84) over 24 hours. During treatment oxygen saturations were significantly higher with NIV-supported ACT (mean difference 2.0, 95% CI 0.9 to 2.6, p=0.0004). No other significant differences were found in post-treatment FEV1, EoC, WoB, oxygen saturations or subject preference. Conclusions: There was no difference in treatment effect between NIV-supported ACT and ACT alone, although the study was underpowered. Oxygen saturations were significantly higher during NIV-supported ACT, but with no effect on post-treatment saturations. NIV was well tolerated. Trial registration number: NCT01885650 .